Teaching and learning innovation in entrepreneurship education: A systematic review of the evidence - Wahid, Ahzilah; Ibrahim, Amlus; Hashim, Norashidah; Chandra, Punitha (Academy for Global Business Advancement (AGBA), 2015)
Innovation in education and entrepreneurship training has been introduced.It was first introduced by Myles Mace at Harvard University through entrepreneurial subjects (Katz, 2003).Until now there are several types of entrepreneurship training conducted in universities and colleges in the United States. These statements are based on the existence of 200 subjects who had been taught in more than 1,600 pieces of these institutions.It includes 277 institutions that provide a venue for entrepreneurial activity, 44 institutions are related to academic research on entrepreneurship and more than 100 hundred founders and financiers for the development of entrepreneurship (Kuratko, 2005).